2001
DOI: 10.4314/sajas.v31i1.3840
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution of the selenium status of herbivores in South Africa

Abstract: Available information on the selenium (Se) status of grazing herbivores in South Africa is reviewed and collated in the form of a geographical distribution map. Marginal to acute Se deficiencies have been reported to occur in the Midlands region and in mountainous areas of the KwaZulu-Natal province and in the southern coastal region of the Western Cape province. These areas receive a high annual rainfall and the soils are predominantly acid. The Se status of livestock in the highland sourveld areas of the Gau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…This study indicates vast areas of Se deficiency. A soil study was conducted, which agrees, to some extent, with the herbivore findings, although relationships are difficult to determine on the map scale (11,37). No studies on Se and HIV/AIDS in Africa have been conducted, (34) even though it has been shown to correlate well (13,34,35).…”
Section: Infectious Diseasesmentioning
confidence: 73%
See 1 more Smart Citation
“…This study indicates vast areas of Se deficiency. A soil study was conducted, which agrees, to some extent, with the herbivore findings, although relationships are difficult to determine on the map scale (11,37). No studies on Se and HIV/AIDS in Africa have been conducted, (34) even though it has been shown to correlate well (13,34,35).…”
Section: Infectious Diseasesmentioning
confidence: 73%
“…The chief biochemical function of Se is to serve as an essential cofactor to the enzyme "guluathione peroxidase" (GSHpx), and Se deficiency may be associated with myopathy, cardiomyopathy, and immune dysfunction (13,36). In South Africa, the importance of Se has been realized in the veterinary industry, and the Se status of herbivores has been determined (37). This study indicates vast areas of Se deficiency.…”
Section: Infectious Diseasesmentioning
confidence: 89%
“…This lack of Se confirms that the lucerne fed to the animals was Se deficient, as they had no access to pastures. This observation emphasizes the need for Se supplementation in regions such as Midlands and mountainous areas of the KwaZulu-Natal province, southern coastal region of the Western Cape where Se is deficient (van Ryssen, 2001) and also during winter times when animals are fed with lucerne that may be produced from this area and other areas that…”
Section: Discussionmentioning
confidence: 81%
“…Van Ryssen ( 2001 ) reviewed the selenium content of South African soils, but during personal discussions in November 2014, he stated that he has no data on selenium concentrations of soil in the Roossenekal area. The poor availability of selenium to plants is well illustrated by a study done to determine the selenium content of maize from South African silos.…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesised that a soil factor, most likely a lowering of the pH, reduced the bioavailability of selenium to vegetation (Courtman et al 2012 ). Soil-buffering capacity can be affected by acid rain and this could play an important role in limiting the bioavailability of selenium in affected areas (Davies & Mundalamo 2010 ; De Villiers & Mkwelo 2009 ; Van Ryssen 2001 ). The Roossenekal area is not far from active industrial areas and is also a site of mining activity.…”
Section: Discussionmentioning
confidence: 99%